2017
DOI: 10.1111/trf.14413
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion in adult palliative care: a systematic review

Abstract: BACKGROUND The risks and benefits of red blood cell (RBC) transfusion in palliative care patients remain poorly understood. We reviewed the literature to summarize available information on RBC transfusion in this population. STUDY DESIGN AND METHODS We searched electronic databases (MEDLINE, Embase, PsycINFO, CINAHL) from inception through September 2016 to identify studies reporting data on palliative patients receiving RBC transfusion. Original studies that assessed RBC transfusion as an intervention and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
(111 reference statements)
1
24
1
1
Order By: Relevance
“…The observed improvement in unadjusted fatigue scores also is consistent with a small, but clinically important change in quality of life. Previous studies have shown that transfusion helps to mitigate the symptoms associated with anemia, an independent predictor of fatigue in oncology and palliative care patients . The RETRO study provides further evidence that RBC transfusion is associated with short‐term, modest improvement in fatigue in hematology/oncology patients.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The observed improvement in unadjusted fatigue scores also is consistent with a small, but clinically important change in quality of life. Previous studies have shown that transfusion helps to mitigate the symptoms associated with anemia, an independent predictor of fatigue in oncology and palliative care patients . The RETRO study provides further evidence that RBC transfusion is associated with short‐term, modest improvement in fatigue in hematology/oncology patients.…”
Section: Discussionmentioning
confidence: 60%
“…RBC transfusion, while necessary and life‐sustaining in patients with cancer, may not overcome the effect of underlying poor health on the quality of life and functional performance outcomes measured in the study. The finding that the effect of transfusion was limited in patients with increased disease burden may be especially important in transfusion decisions at the end of life in the palliative care setting …”
Section: Discussionmentioning
confidence: 99%
“…The panel decided to use indirect evidence, obtained from 2 published systematic reviews of the literature, neither of which was focused on older adults with AML, to inform this question. 163,164 The first systematic review focused on the effects of RBC transfusions for patients receiving palliative care. 163 The mean age of patients included in the studies ranged from 64 through 70 years, and it was specified (only in some of the studies) that the patients had terminal malignancies or advanced nonmalignant disease.…”
Section: Recommendationmentioning
confidence: 99%
“…In this issue of TRANSFUSION , Chin‐Yee and colleagues report a systematic literature review of red blood cell (RBC) transfusion in patients receiving palliative care . They importantly highlight that, although RBC transfusion may provide symptomatic relief and subjective improvements to some patients, there is a paucity of high‐quality evidence at this time to substantively guide or support the use of this therapy during end‐of‐life care.…”
mentioning
confidence: 99%
“…1 They importantly highlight that, although RBC transfusion may provide symptomatic relief and subjective improvements to some patients, there is a paucity of high-quality evidence at this time to substantively guide or support the use of this therapy during end-of-life care. In addition, the risks of RBC transfusion in this unwell, diverse patient population are poorly characterized, making the task of conducting a proper risk-benefit analysis by ordering providers difficult.…”
mentioning
confidence: 99%